2008
DOI: 10.1002/ajmg.b.30855
|View full text |Cite
|
Sign up to set email alerts
|

The impact of individual and methodological factors in the variability of response to methylphenidate in ADHD pharmacogenetic studies from four different continents

Abstract: Several studies have evaluated the association between individual polymorphisms and response to methylphenidate (MPH) in subjects with attention-deficit/hyperactivity disorder (ADHD). There are few replication studies for each polymorphism of interest and results are sometimes inconsistent in this field. Although data collection from multiple international sites would allow large sample sizes, this approach has been criticized for introducing sampling variability due to differences in ethnicity and methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 36 publications
1
16
0
2
Order By: Relevance
“…Similar differences of pharmacogenetic effects in ADHD-treated subjects between randomised clinical trials and naturalistic studies have been reported previously. 27 As randomised clinical trials control for placebo effects by including a control group, they are generally considered to be the superior experimental approach to the investigation of pharmacological effects. Even if in the case of the presented pharmacogenetic studies potential placebo effects Overall, however, these results suggest that the often-examined 40 bp VNTR in the 3 0 -untranslated region of the SLC6A3 gene does not significantly relate to quantitative measures of treatment success with methylphenidate in ADHD, with the exception of studies using naturalistic designs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar differences of pharmacogenetic effects in ADHD-treated subjects between randomised clinical trials and naturalistic studies have been reported previously. 27 As randomised clinical trials control for placebo effects by including a control group, they are generally considered to be the superior experimental approach to the investigation of pharmacological effects. Even if in the case of the presented pharmacogenetic studies potential placebo effects Overall, however, these results suggest that the often-examined 40 bp VNTR in the 3 0 -untranslated region of the SLC6A3 gene does not significantly relate to quantitative measures of treatment success with methylphenidate in ADHD, with the exception of studies using naturalistic designs.…”
Section: Discussionmentioning
confidence: 99%
“…26 The reasons for this response variability among patients are unclear, but are likely to be multifactorial. Although interstudy methodological issues may play a role for observed variability in the literature, 27 the present study aims to clarify the role of pharmacogenetics in interindividual response variability. Pharmacogenetics refers to the association between genetic variation and the magnitude of response to treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variations in study design may be partially responsible for the disparate findings, since a recent meta-analysis of ADHD pharmacogenetics investigations determined that the design of the study (open-label studies vs. randomized controlled trials) was significantly associated with heterogeneity of results. [47] Concerns raised regarding retrospective, observational pharmacogenetic studies have included biased ascertainment of outcome,[48] as well as a tendency to underestimate environmental contributions and overestimate genetic effects. [49] Therefore, in this article, results of double-blind, placebo-controlled trials are presented separately from those of naturalistic studies for each genetic polymorphism.…”
Section: Adhd Pharmacogenetic Research Studiesmentioning
confidence: 99%
“…There are concerns that small sample sizes, study design variations (open-label vs. randomized controlled trials), outcome measure differences, sample differences, and varying dosing regimens may be partially responsible for the disparate findings to date. 8,9,41,42 For example, only three ADHD pharmacogenetic studies in school-age children have been randomized, placebo-controlled, and double-blinded. 1820 Only two school-age 19,33 and one preschool trial 32 have used parent and teacher outcome ratings.…”
Section: Introductionmentioning
confidence: 99%